Has Higher Household Indebtedness Weakened Monetary Policy Transmission? - Gelos, R. (IMF Working Papers; Working Paper, 2019)
Has monetary policy in advanced economies been less effective since the global financial crisis because of deteriorating household balance sheets? This paper examines the question using household data from the United States. It compares the responsiveness of household consumption to monetary policy shocks in the pre- and post-crisis periods, relating changes in monetary transmission to changes in household indebtedness and liquidity. The results show that the responsiveness of household consumption has diminished since the crisis. However, household balance sheets are not the culprit. Households with higher debt levels and lower shares of liquid assets are the most responsive to monetary policy, and the share of these households in the population grew. Other factors, such as economic uncertainty, appear to have played a bigger role in the decline of households' responsiveness to monetary policy.